2014
DOI: 10.4103/0973-1482.145856
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential biomarkers for clear cell renal cell carcinoma based on microRNA-mRNA pathway relationships

Abstract: This integrative network approach revealed important miRNAs in the ccRCC that can identify specific disease biomarkers, which can be used as targets for cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Though numerous studies have been focused on miRNAs, the functions of most miRNAs remain poorly understood. MiRNA-320d (miR-320d) is a member of miRNA-320 family, and acts as a tumor suppressor but has a very low expression level in several human malignant tumors [14][15][16]. However, very few researches have focused on this miRNA effects on gastric cardia adenocarcinoma (GCA).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though numerous studies have been focused on miRNAs, the functions of most miRNAs remain poorly understood. MiRNA-320d (miR-320d) is a member of miRNA-320 family, and acts as a tumor suppressor but has a very low expression level in several human malignant tumors [14][15][16]. However, very few researches have focused on this miRNA effects on gastric cardia adenocarcinoma (GCA).…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies have reported the functions of miR-320d in several cancer types, such as colorectal cancer [15], renal cell carcinoma [16], glioma [23], et al, less studies are focusing on the potential targeted genes of miR-320d. As the classical function of microRNA is silencing targeted genes by completely or incompletely pairing to the 3′-UTR of the specific genes, we screened the miR-320d targeted genes through the TargetScan website and other microRNA databases, and eventually found that FoxM1 contains two mRNA 3′-UTR binding sites for miR-320d.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And the present review highlighted the role of glutathione and related cytoprotective effects in the susceptibility to carcinogenesis and in the sensitivity of tumors to the cytotoxic effects of anticancer agents [ 40 ]. Recently, Hao et al discovered that three significant pathways related to ccRCC, namely, arginine and proline metabolism, aldosterone-regulated sodium reabsorption, and oxidative phosphorylation, were observed [ 41 ]. Arginine/proline metabolism is a significant pathway in ccRCC that had been discovered by Perroud et al previously [ 42 ], and the results were in accordance with our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…miR-425-5p is located on human chromosome 3 and is aberrantly expressed in various types of cancer, including gastric ( 9 ), cervical ( 10 ) and hepatocellular carcinoma ( 11 ). Reverse transcription quantitative polymerase chain reaction (RT-qPCR) analysis indicated an overexpression of miR-425-5p in RCC tissues, thus suggesting its potential use as a biomarker for the diagnosis of RCC ( 12 , 13 ). However, the molecular mechanisms underlying the effects miR-425-5p in RCC remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%